2016
DOI: 10.1016/j.nanoen.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic insights into the nature of active sites in iron–nitrogen–carbon electrocatalysts for oxygen reduction in acid

Abstract: embedded iron particles that are not directly involved in the oxygen reduction pathway. The high ORR activity and durability of catalysts involving this second site, as demonstrated in fuel cell, are attributed to the high densityof active sites and the elimination or reduction of Fenton-type processes. The latter are initiated byhydrogen peroxide but are known to be accelerated by iron ions exposed to the surface, resulting in the formation of damaging free-radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
219
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(233 citation statements)
references
References 84 publications
10
219
1
Order By: Relevance
“…Having previously shown that Ni 3 (HITP) 2 reduces O 2 electrocatalytically in strongly basic medium (0.1 M KOH), we explored its utility over the wider aqueous pH range and found that the material is competent for ORR catalysis under all alkaline conditions (pH 8 and above), but not in acidic medium. Indeed, cyclic voltammograms (CVs) of Ni 3 (HITP) 2 above pH 8 showed catalytic waves with no loss in current density over 20 cycles, whereas catalytic current decreased with every cycle in acidic media (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having previously shown that Ni 3 (HITP) 2 reduces O 2 electrocatalytically in strongly basic medium (0.1 M KOH), we explored its utility over the wider aqueous pH range and found that the material is competent for ORR catalysis under all alkaline conditions (pH 8 and above), but not in acidic medium. Indeed, cyclic voltammograms (CVs) of Ni 3 (HITP) 2 above pH 8 showed catalytic waves with no loss in current density over 20 cycles, whereas catalytic current decreased with every cycle in acidic media (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Indeed, cyclic voltammograms (CVs) of Ni 3 (HITP) 2 above pH 8 showed catalytic waves with no loss in current density over 20 cycles, whereas catalytic current decreased with every cycle in acidic media (Figure 2). …”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These can be distinguished from hydrophilic pores of low contact angle that are water-filled. 39 Dashed lines indicate deconvolution of distributions into three (NPC-2000) 33 and two (MOF SR) log-normal distributions with mean radius, r 0 , and volume fractions indicated in the table.…”
Section: Standard 5cmmentioning
confidence: 99%
“…Thanks to their versatility, they have found a range of exciting applications in spintronics [225][226][227][228][229][230], optoelectronics [231,232], solar cells [233][234][235][236][237][238], and as building blocks of magnetic materials [239][240][241][242][243]. In addition, porphyrin-like centers can be embedded in graphene and carbon nanotubes to be used for oxygen reduction catalysis [244][245][246][247][248][249]. A recent proposal suggests it might be possible to realize topologically protected excitonic states in porphyrin thin films [250].…”
Section: Introductionmentioning
confidence: 99%